Halogen-Radical-Promoted Dearomative Aza-Spirocyclization of Alkynylimines: An Efficient Approach to 3-Halo-Spirocyclohexadienones - Chen, Dianpeng; Li, Jianming; Shan, Yingying; Cui, Peiying; Zhao, Yutong; Tian, Laijin; Qiu, Guanyinsheng (Synthesis, 2020)
A novel halogen-radical-promoted dearomative aza-spirocyclization of alkynylimines for the synthesis of 3-halo-spirocyclohexadienones is described. In this process, it is believed that a radical addition, 5-exo-trig cyclization, and dearomative aza-spirocyclization are involved. Easily available starting materials, mild conditions, and a wide substrate scope make this approach potentially useful.
Keywords: halogen radical; dearomative aza-spirocyclization; alkynylimine; 3-halo-spirocyclohexadienone; 5-exo-trig cyclization